1996
DOI: 10.3109/10253899609001093
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Behaviour and Body Weight Following a Single or Double Social Defeat in Rats

Abstract: In a series of experiments, the consequences of a single and double social conflict on various behaviours and body weight in rats were studied. Animals were subjected to social defeat by placing them into the territory of an aggressive male conspecific for one hour, either once, or twice at the same time on two consecutive days. To assess the consequences of social defeat, three experiments were performed with independent groups of rats. In the first experiment, an open field test was performed two days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
115
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(134 citation statements)
references
References 39 publications
13
115
0
6
Order By: Relevance
“…In rats, social defeat results in decreased body weight gain following acute social defeat as well as decreased food intake that persists for several days after the defeat session [22]. In studies using restraint stress, rats lose weight and remain hypophagic for several days after the stressor has ended [23].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, social defeat results in decreased body weight gain following acute social defeat as well as decreased food intake that persists for several days after the defeat session [22]. In studies using restraint stress, rats lose weight and remain hypophagic for several days after the stressor has ended [23].…”
Section: Introductionmentioning
confidence: 99%
“…These studies clearly showed that this paradigm provides a powerful and realistic methodology to study strategies to cope with naturalistic stress [9]. In rodents a social defeat affects the organism both at the physiological and behavioral level [9,11], with a general increase in sympathetic activity (heart rate and body temperature) lasting from one to several hours [12] and an impairment of social and explorative activity lasting up to several weeks [14]. Effects of social defeat have never been tested in birds although it is known that nestlings' activity and heart rate are very sensitive to an alarm call [18], which in many species is often emitted during fights.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, most of the work is restricted to mammals, in particular rodents and primates, exposed to severe or chronic stress procedures (e.g., prolonged social isolation, housing in overcrowded environments or early maternal separation) very unlikely to occur in the real world. An attempt to modify this approach has been made by testing the effect of social defeat in territorial animals, mainly rodents [11,14,15,17,19]. These studies clearly showed that this paradigm provides a powerful and realistic methodology to study strategies to cope with naturalistic stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…uncontrollable stressors have been shown to induce changes in a wide variety of behavioral parameters, including decreases in general locomotor activity and explorative behavior as well as impairment of sexual behavior, feeding, and drinking (27). Social stressors can be uncontrollable.…”
mentioning
confidence: 99%